Active fault-tolerant control approach design for rigid spacecraft with multiple actuator faults. (November 2018) - Gao, Zhifeng; Cheng, Peng; Qian, Moshu; Jiang, Guoping; Lin, Jinxing
In this study, the active fault-tolerant control problem is investigated for a rigid spacecraft in the presence of inertia uncertainty, external disturbance, multiple actuator faults and actuator saturation. The attitude system model of spacecraft and actuator fault model are first given. A sliding mode–based fault detection observer and a radial basis function neural networks–based fault estimation observer are designed to detect the time of actuator fault occurred and estimate the amplitude of unknown fault, respectively. On that basis, an active fault-tolerant control scheme is proposed to accommodate the effects of multiple actuator faults, and it guarantees that the state trajectory of attitude systems without actuator saturation converges to a neighborhood of the origin in finite time. Another active fault-tolerant control scheme is further proposed in actuator saturation constraint case; it ensures that all the closed-loop signals are finite time convergence. Finally, simulation results are given to illustrate the effectiveness of the proposed fault-tolerant control approach.